The surgical management of patellofemoral instability: when is an isolated medial patellofemoral ligament reconstruction indicated?. Issue 3 (May 2016) - Jain, Neil
Abstract : Many factors contribute to patellofemoral instability. Surgical intervention may include additional procedures to reconstruct the medial patellofemoral ligament (MPFL). This review attempts to ascertain from the literature whether there is a threshold for when an isolated MPFL reconstruction will suffice and when an additional procedure would be required.